Oxidative stress and growth temperature in Bacillus subtilis. - DEVINE, KEVIN; MC CONNELL, DAVID JOHN (My University, 1987)
Pretreatment of Bacillus subtilis with low concentrations of hydrogen peroxide protected the cells against the lethal effects of higher levels of oxidative stress. During the period of adaptation, eight proteins were induced, as detected by one-dimensional gel electrophoresis. Four of these proteins were the same size as four of the proteins induced by the temperature upshift. The range of proteins synthesized in response to an elevation in temperature depended both on the starting (lower) temperature and on the temperature to which the cells were shifted. Both catalase and superoxide dismutase were present at high levels in B. subtilis, but neither was induced by oxidative stress or temperature upshift. In fact, catalase activity was reduced after the temperature upshift
PUBLISHED
Keywords: Genetics